If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6+4(1-v)=-3(v+2)
We simplify the equation to the form, which is simple to understand
-6+4(1-v)=-3(v+2)
Reorder the terms in parentheses
-6+(+4-4v)=-3*(v+2)
Remove unnecessary parentheses
-6+4-4v=-3+*(+v+2+)
Reorder the terms in parentheses
-6+4-4v=+(-3v-6)
Remove unnecessary parentheses
-6+4-4v=-3v-6
We move all terms containing v to the left and all other terms to the right.
-4v+3v=-6+6-4
We simplify left and right side of the equation.
-1v=-4
We divide both sides of the equation by -1 to get v.
v=4
| -2x+7=8-(1+4x) | | 4x45/6 | | 2-3z=7(8-2z)+12 | | -11-9+0=-20 | | .5(6)+y=1 | | 3(h+5)=3h+15 | | 8x-25=2-3x+5-5x | | 3(2q+7)=15(p-4) | | -(x+8)+1=5(7-3x) | | 2+(-9)-(-4)= | | -69=7v-5 | | (r+5/3)=20 | | -6y-2=3-5y | | 4m+8+5(3m-5)-5(m+5)=0 | | 2y-6=5y+6 | | (X-3)x=550 | | 7-3x=7-4x+x | | 2x-2=18x+6 | | 30+34-x=13x-5x+37 | | 2z+5=4x-9 | | 1-(-4-n)=3(n+3) | | 5x^2+20xy-40y= | | 9-(-9)+(-4)= | | x+2x+6x+3=21 | | 4y^3-5y^2-12y+15= | | Y(7+3)=5 | | (-7)+2+(-5)= | | -2(1-3x)-x=-2-6x | | 4y^3-5y^2-12y-15= | | 5(a-12)+(2a+15)=a-9 | | 8x-7x=-(1-2x)-7(x+5) | | 5/3x-5=3x+7 |